Micromagnetic Study on the Magnetization Reversal of Barium Hexaferrite (BaFe12O19) Thin Film - Djuhana, Dede; Oktri, Dita; Kurniawan, Candra (Makara Journal of Science, 2018)
This study investigates a magnetization reversal mechanism based on the hysteresis curve of Barium Hexaferrite (BFO) thin film by micromagnetic simulation through parallel and perpendicular magnetization directions along the axes. The hexagonal shape of the BFO film was modeled with thicknesses of 5, 10, and 15 nm and a diameter size ranging from 50 to 100 nm. It was found that the coercivity field HC and the saturation field HS of the BFO film decreased as thediameter size increased and thickness decreased. It was observed that the nucleation field HN increased as the diametersize increased. An analysis of energies showed that the demagnetization energy was dominantly influenced by the diameter and thickness in comparison to the anisotropic energy. From the hysteresis curve, the switching time was also investigated. Interestingly, the switching time was faster for the thinner BFOs with a diameter under 70 nm. For particles larger than 70 nm in diameter, the switching time showed fluctuation irrespective of the BFO thickness. Based on these results, a diameter size of 70 nm is proposed as the critical size for producing the equal time for switching domain polarity.